2020
DOI: 10.1097/scs.0000000000006167
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Maxillary Movements on Nasal Aesthetics Following Orthognathic Surgery

Abstract: Improvement of the harmony between facial subunits is the ultimate goal of orthognathic surgery and surgeons must accurately make soft tissue projections for planned bony movements. Yet, few studies have examined the effects’ of orthognathic surgery on aesthetic parameters of nasolabial area on a thorough basis. This retrospective study included 61 patients that underwent orthognathic surgery. Demographic data, evaluation period, and surgical details were analyzed. Superficial topographical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Open or closed rhinoplasty can thus be combined with liplift, as previously reported, with both cutaneous and endonasal incision, as the chance to perform multiple surgical corrections during a single operating session is of great benefit for both the patient and the surgeon. 36 The major concern about one or two incisions, along with the fear of columellar necrosis, is no longer the case since several authors confirmed the safety of both approaches and that the scar is no longer visible after a proper healing period (►Figs. 14-16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open or closed rhinoplasty can thus be combined with liplift, as previously reported, with both cutaneous and endonasal incision, as the chance to perform multiple surgical corrections during a single operating session is of great benefit for both the patient and the surgeon. 36 The major concern about one or two incisions, along with the fear of columellar necrosis, is no longer the case since several authors confirmed the safety of both approaches and that the scar is no longer visible after a proper healing period (►Figs. 14-16).…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of lip shortening and NLA widening recorded in the study population have here been presented as a percentage since authors believe that direct linear measurements are not paramount when assessing facial proportions, as their variability is found in multiple papers. 2,3,12,20,25,31,36 Finally, the described procedure's aim is to rejuvenate the lip through its shortening. Patients, however, mostly appreciate lip eversion and projection along with the perception of an increased fullness.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many studies about the effect of maxillary movements on soft tissue, very few of these studies provide specific information about the change in nasal morphology. 6,7,16,18,20 In this study, how ''Gull in Flight'' appearance is affected postoperatively was investigated together with other specific parameters related with nasal aesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…22 There were a few studies in the literature examining the relation of the columella lobular angle with maxillary movements. 16,18,23 Gencay et al 18 stated columella lobular angle was increased following maxillary impaction, advancement, and rotation but inferior position of maxilla decreased this angle. However, these changes were not found statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation